Interactive parallel fluid solver using the Lattice-Boltzmann method and CUDA (2010)
Particle methods have been gaining momentum in the Computational Fluid Dynamics world, for their computational simplicity and inherent parallelism -- This has lead the field to jump to new hardware technologies that exploit the parallelism in a whole new way -- This project is an interactive parallel implementation of the Lattice Boltzmann Method that runs on a hyper parallel architecture as a modern GPU and uses CUDA technology for its implementation -- First the mathematical concepts of the method are introduced, then the implementation is done using the SIMD paradigm, to later on attack the visualization and interactivity simple way